An examination of the sonnets of E.E. Cummings - Hughes, Jeremy Francis (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1992)
This dissertation examines E. E. Cummings's writings in the sonnet genre and in those genres to which the sonnet is related in various ways. Its fundamental point is that, despite the surface impression of poetic iconoclasm for which Cummings has a popular reputation, in choosing to write sonnets he engages in a traditional literary practice. He does this because his purpose is always to be an artist, as defined by the Aesthetic movement which influenced him. In order to argue his embracing of a traditional artistic role, the theory of genres espoused by Alastair Fowler in his book, Kinds of Literature, is used. Chapter 1 of the thesis comprises general introductory material, both to the range of Aesthetic ideas to which Cummings subscribed, and to Fowler's theory of genres. Several key generic kinds are also described. The second chapter makes use of two of these generic models, the sonnet sequence and the silva, as a way of examining Cummings's deployment of the sonnet within the larger context of his poetry collections. It is a survey of the structure of the anthologies he compiled from Tulips & Chimneys (1922) to 95 Poems (1958). The third chapter explores the three sonnet modes which Cummings first identifies and names when compiling the manuscript of Tulips & Chimneys, and continues to use in his collections up to and including is 5 (1926). Chapter 4 shows how certain themes and concerns from these early sonnets are altered and synthesised as Cummings matures from an aesthete to a Romantic poet. Sonnets from his later books are taken to be representative of three central kinds in all of his work after is 5. Chapters 3 and 4 proceed by means of relatively close readings of individual sonnets. This practice fulfils a double role: it penetrates the apparent obscurity of the more difficult poems, and it attempts to preserve the integrity of individual poems which exemplify different generic tendencies in Cummings's work. One of Cummings's reasons for writing sonnets is that the form favours the achievement of what Wordsworth calls "a feeling of intense unity". In undertaking close readings of a few sonnets I have attempted to preserve that feeling.
Keywords: Cummings, E. E. (Edward Estlin), 1894-1962 -- Criticism and interpretation; Sonnets, English -- Criticism and interpretation